Miscommunication between patients and general practitioners: implications for clinical practice - Morgan S (CSIRO Publishing, 2013)
INTRODUCTION: Effective communication is integral to the general practice consultation, yet it is acknowledged that problems commonly occur. Previous research has shown that misunderstandings with potentially significant consequences occur frequently, but does not provide a clear picture of how and why miscommunication occurs, or how such problems can be prevented or resolved. This study explored the occurrence and management of specific examples of miscommunication in two routine general practice consultations. METHODS: A multi-method case study approach was used. The primary data collected for each case included a video-recorded consultation and post-consultation interviews with each general practitioner (GP) and patient. Instances of communication mismatch were examined using in-depth interaction analysis techniques. FINDINGS: GPs and patients may not be aware when misunderstandings have occurred. In-depth analysis of the case studies revealed the complexity of miscommunication: it was not a straightforward matter to locate when or why instances of communication mismatch had occurred, and each of the mismatches was quite distinctive: (1) they were identified in different ways; (2) they occurred at different points in the communication process; (3) they arose because of problems occurring at different levels of the communication, and (4) they had different consequences. CONCLUSION: Given the frequency and complexity of miscommunication in general practice consultations, GPs need to consider adopting various strategies, at both the practice/systems level and the level of the consultation interaction to minimise the risk of communication problems.